Postoperative Euglycemic Diabetic Ketoacidosis and Encephalopathy Related to SGLT-2 Inhibitors: A Case Report and Discussion of Diabetes Treatment and "Sweet Pee Encephalopathy" in Perioperative Hospital Management. (January 2020) - Mackintosh, Christopher; Tewari, Arti; Siegel, Jason; Wang, R. Doris; Freeman, William
During preanesthesia evaluation, patient medications are reviewed and many are not administered on the day of surgery. Additionally, neurosurgical patients can develop postoperative encephalopathy from a variety of etiologies, including metabolic derangements. We report a case of postoperative neurosurgical euglycemic ketoacidosis which presented as unexplained encephalopathy and was the result of continued action of the patient's serum glucose cotransporter-2 (SGLT-2) inhibitor combined with perioperative fasting. A 68-year-old woman with a history of type 2 diabetes mellitus was admitted to the neurocritical care service after resection of a left temporal meningioma. On postop day 1, she became lethargic and with worsening aphasia. Laboratory studies revealed blood glucose 140 to 160 mmol/L, bicarbonate 9 mmol/L, anion gap of 21, and pH of 7.2. Urine was positive for ketones and glucose, and serum was positive for β-hydroxybutyrate. Endocrinology was consulted and the patient was diagnosed with euglycemic diabetic ketoacidosis and treated with insulin until her anion gap closed. Over the next 2 days, her neurological examination improved to baseline. Although the patient did not take empagliflozin the day of surgery, the drug has a half-life of >12 hours, and other reports have described continued glycosuria for up to 10 days after drug discontinuation. This case illustrates the need for increased awareness of SGLT-2 inhibitors and "sweet pee encephalopathy" among neurosurgical and neurointensivist teams as well as potential modification of perioperative management of patients using newly emerging SGLT-2 inhibiting pharmaceuticals.